Varicella Outbreak in an Indian Couple Living in Germany Caused by VZV Clade VI Acquired during a Trip to The Netherlands - Malgorzata Kolesnik; Bernd Bonnekoh; Ina Tammer; Harald Gollnick; Andreas Sauerbrei (Case Reports in Medicine)
Varicella-zoster virus (VZV), the cause of varicella and zoster, is divided into five major clades and four provisional clades, the latter of which have been rarely reported worldwide to date. We present a varicella outbreak by the provisional clade VI within an Indian couple in Germany returning from a trip to Amsterdam. To the best of our knowledge, this is the first case of varicella by the VZV clade VI described in Germany, but the disease was acquired in The Netherlands.